Refinement checking for privacy policies - Papanikolaou, N; Creese, S; Goldsmith, M (2012)
This paper presents a framework for analysis and comparison of privacy policies expressed in P3P (Platform for Privacy Preferences). In contrast to existing approaches to policy analysis, which focus on demonstrations of equality or equivalence of policies, our approach makes it possible to check for refinement between policies. We automatically generate a CSP model from a P3P policy, which represents the policy's intended semantics; using the FDR model checker, we then perform various tests (using process refinement) to determine (a) whether a policy is internally consistent, and (b) whether a given policy refines another by permitting similar data collection, processing and sharing practices. Our approach allows for the detection of subtle differences between practices prescribed by different privacy policies, the comparison of relative levels of privacy offered by different policies, and captures the semantics of policies intended in the original P3P standard. The systematic translation of policies to CSP provides a formal means of reasoning about websites' privacy policies, and therefore the practices of various enterprises with regards to personal data. © 2011 Elsevier B.V. All rights reserved.